Diamond / metal joint and femtosecond laser modification-based brazing method thereof
By forming a graphite layer on the surface of diamond and depositing active elements, the problem of insufficient bonding strength between diamond and metal was solved, achieving stable interface connection at high temperatures and improving the reliability and lifespan of the device.
Patent Information
- Application Number
- CN202511294211.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-11
- Publication Date
- 2025-11-04
AI Technical Summary
Diamond has a weak bond strength with metals, which makes it prone to interface delamination failure under high-temperature service conditions, affecting the reliability of the device.
A graphite layer is formed by scanning the diamond surface with a femtosecond laser, an active layer is formed by magnetron sputtering of active elements, and then brazing is performed after vacuum heat treatment at 500 to 800°C.
It significantly improves the interfacial bonding strength between diamond and metal, avoids interfacial cracking at high temperatures, achieves reliable low-temperature connection, and enhances the long-term stability of the device.
Smart Images

Figure CN120885791A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of material processing and connection, in particular to a diamond / metal joint and a brazing method based on femtosecond laser modification. BACKGROUND
[0002] Diamonds exhibit great application potential in the field of high-power electronic device heat dissipation due to their excellent physical and chemical properties, including ultrahigh thermal conductivity, extremely low thermal expansion coefficient, and excellent chemical stability. However, the covalent bond structure of the diamond surface leads to its strong chemical inertness, which in turn results in a generally weak bonding strength between the metal and the diamond surface, posing a major challenge to the reliable connection of the diamond and the metal. SUMMARY
[0003] The present application aims to solve the problem of weak bonding strength between the metal and the diamond surface.
[0004] To solve the above problem, the present application provides a diamond / metal joint and a brazing method based on femtosecond laser modification.
[0005] In a first aspect, the present application provides a brazing method for diamond and metal based on femtosecond laser modification, comprising the following steps: S1: scanning treatment is performed on the diamond surface using a femtosecond laser to form a graphite layer on the diamond surface; S2: active elements are magnetron sputtered on the surface of the graphite layer to deposit an active layer; S3: vacuum heat treatment is performed on the diamond at 500-800℃, and then the diamond is brazed with the metal.
[0006] Optionally, the wavelength of the femtosecond laser is 1000-1100 nm, the pulse width is 200-300 fs, and the repetition frequency is 100-500 kHz.
[0007] Optionally, the energy density during the scanning treatment is 5-15 J / cm 2 , the scanning rate is 100-500 mm / s, and the light spot overlap rate is 50-70%.
[0008] Optionally, step S2 comprises: Magnetron sputtering of a first active element as a bonding layer on the surface of the graphite layer, followed by deposition of a second active element as a diffusion barrier layer, and the combination of the bonding layer and the diffusion barrier layer as the active layer.
[0009] Optionally, the first active element is one or more of Ti, Cr, W, and Zr, and the second active element is one or more of Mo, W, and Zr.
[0010] Optionally, the vacuum degree during the process of magnetron sputtering the first active element as the adhesive layer is not more than 5*10 -4 The substrate temperature of the diamond is 150-250℃, the sputtering power is 80-150 W, and the sputtering time is 30-120 min.
[0011] Optionally, the vacuum degree during the process of depositing the second active element as the diffusion barrier layer is not more than 5*10 -4 Pa, the deposition power is 80-150 W, and the deposition time is 30-120 min.
[0012] Optionally, the thickness of the adhesive layer is 0.2-1.0 μm, and the thickness of the diffusion barrier layer is 0.2-1.0 μm.
[0013] Optionally, the vacuum degree during the process of vacuum heat treatment is not more than 5*10 -4 Pa, and the treatment time is 30-90 min.
[0014] In the second aspect, the application provides a diamond / metal joint made by the brazing method of the diamond and metal based on femtosecond laser modification as described above.
[0015] The diamond / metal joint and the brazing method of the diamond and metal based on femtosecond laser modification have the following beneficial effects: the femtosecond laser can realize non-thermal precise etching of the diamond surface due to the characteristics of ultra-short pulse (10 -15 s level) and ultra-high peak power, induce sp 3 carbon to sp 2 graphite phase conversion, controllably form a nano-graphite transition layer, significantly improve the surface chemical activity, and significantly enhance the chemical bonding strength between the active element layer and the diamond, the active element reacts with the nano-graphite layer to form a continuous active element-C compound, the crystal lattice of which is partially coherent with the diamond, realizing strong metallurgical bonding; at the same time, from the perspective of thermodynamics, the Gibbs free energy of the reaction between the active element and the graphite layer is much lower than that of the reaction between the active element and the diamond, so the nano-graphite layer can reduce the thermodynamic requirement of active element-C formation, promote the interface reaction to realize stronger interface bonding force, and further improve the reliability of the brazed joint; the plastic deformation capacity of the graphite layer is better than that of the diamond, the nano-graphite transition layer can absorb the interface thermal stress, has a stress buffering effect, and inhibits crack initiation. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 The flowchart of the brazing method of the diamond and metal based on femtosecond laser modification of the embodiment of the application; Figure 2 The electron microscope schematic diagram of the diamond interface of Example 1; Figure 3Raman spectrum of the diamond of Example 1 detected before the treatment with femtosecond laser; Figure 4 Raman spectrum of the diamond of Example 1 detected after the treatment with femtosecond laser; Figure 5 Schematic diagram of cross-section transmission electron microscopy of the Cr3C2 layer of the diamond interface of Example 1. DETAILED DESCRIPTION
[0017] In order to make the above objectives, characteristics and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application will be described in detail below with reference to the drawings. Although some embodiments of the present application are shown in the drawings, it should be understood that the present application can be implemented in various forms, and should not be interpreted as being limited to the embodiments described herein, on the contrary, these embodiments are provided in order to more thoroughly and completely understand the present application. It should be understood that the drawings and embodiments of the present application are only for exemplary purposes, and are not intended to limit the scope of protection of the present application.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present application belongs. The terms used in the specification of the present application are only for the purpose of describing the specific embodiments and are not intended to limit the present application; The term "comprising" and variations thereof as used herein are open-ended, that is "including but not limited to"; the term "based on" is "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". Related definitions of other terms will be given in the following description. In the description of the present application, the meaning of "a plurality of" is two or more, unless otherwise stated.
[0019] In the related art, the bonding force between the magnetron sputtered metalized layer and the diamond surface is generally weak, and interfacial delamination failure easily occurs under high temperature service conditions, seriously affecting the working reliability of the device. At present, the industry mainly adopts two technical routes to solve this problem: the active brazing method can form a carbide layer through high temperature interfacial reaction, but has obvious limitations, including high brazing temperature leading to graphitization damage of the diamond, and excessive residual stress affecting the joint performance; the surface metallization method improves the interfacial properties through multi-layer structure design, but the bonding strength of the active layer and the diamond substrate is still insufficient, and micro-crack defects easily occur during subsequent heat treatment, which restricts the long-term stability of the joint. These technical bottlenecks seriously limit the application effect and service life of diamond in high-performance heat dissipation devices.
[0020] In view of the problems in the above related technologies, the embodiments of the present application provide a diamond / metal joint and a brazing method based on femtosecond laser modification.
[0021] As Figure 1 shown, an embodiment of the present application provides a brazing method of diamond and metal based on femtosecond laser modification, including the following steps: S1: scanning treatment is performed on the surface of the diamond by using a femtosecond laser to form a graphite layer on the surface of the diamond; S2: active elements are magnetron sputtered on the surface of the graphite layer to deposit an active layer; S3: vacuum heat treatment is performed at 500-800 DEG C, and then the diamond is brazed with the metal.
[0022] In the embodiment, the femtosecond laser can realize non-thermal melting precise etching on the surface of the diamond due to the characteristics of ultrashort pulse (10 -15 s level) and ultrahigh peak power, induce sp 3 carbon to sp 2 graphite phase conversion, controllably form a nanometer graphite transition layer, significantly improve the surface chemical activity, and significantly enhance the chemical bonding strength between the active element layer (Ti, Cr, W or Zr, etc.) and the diamond, and the active element and the nanometer graphite layer react to generate a continuous active element-C compound (about ΔG_f = -180 kJ / mol), the lattice of which is partially coherent with the diamond (lattice mismatch degree < 5%), realizing strong metallurgical bonding; at the same time, from the thermodynamic point of view, the Gibbs free energy of the reaction between the active element and the graphite layer is much lower than that of the reaction between the active element and the diamond, so the nanometer graphite layer reduces the thermodynamic requirement of the active element-C, promotes the interface reaction to realize stronger bonding force at the interface, and further improves the reliability of the brazed joint; the plastic deformation capacity of the graphite layer is better than that of the diamond, and the nanometer graphite transition layer can absorb the thermal stress at the interface, has a stress buffering effect, and inhibits crack initiation.
[0023] The bonding strength between the graphite layer formed by femtosecond laser modification and the substrate is improved by about three times, solving the problem of interface cracking during heat treatment. Reliable connection of the diamond and the metal at low temperature is realized, high-strength interface is obtained while material thermal damage is inhibited. The graphite layer formed by femtosecond laser modification significantly improves the surface reactivity, so that the active metal layer and the substrate form chemical bonding; the gradient transition layer constructed by the magnetron sputtering process effectively relieves thermal stress; the optimized brazing temperature range takes into account the requirements of metallurgical reaction and material protection, providing a new way for the manufacture of high-thermal-conductivity devices.
[0024] Specifically, the femtosecond laser scanning process refers to a process of inducing phase transition on the surface of diamond by using an ultrashort pulse laser beam, and can be realized by using a laser with a wavelength of 1000 to 1100 nm and a pulse width of 200 to 300 fs. The process forms a controllable thickness of graphite layer on the surface layer by a non-thermal melting mechanism, and provides a chemically active interface for subsequent metal deposition. The magnetron sputtering active element refers to a process of depositing active metal atoms on the surface of the substrate by plasma bombarding the target material, and can be realized by using a sputtering chamber with a vacuum degree of less than 5*10 -4 Pa. The active layer formed by the process not only enhances the interface bonding force, but also serves as a thermal expansion coefficient transition layer. The brazing temperature range of 500 to 800 DEG C refers to the operating interval below the critical temperature of diamond graphitization, and can be realized by using a vacuum brazing furnace with silver-based filler. The temperature window can not only ensure the formation of metallurgical bonding, but also avoid the destruction of the diamond structure.
[0025] The ultrashort pulse characteristics of femtosecond laser enable the energy to be deposited within picosecond time, and break the diamond sp 3 hybrid bond through multi-photon absorption effect, forming a continuous graphite layer within a depth of about 200 nm on the surface layer. The modified layer has higher chemical activity than the original diamond surface, so that the titanium element of magnetron sputtering can form stable Ti-C chemical bond. In the subsequent brazing process, the titanium element in the active layer diffuses into the filler, forms Cu-Ti intermetallic compound with the copper substrate, and realizes reliable connection of diamond and metal. The whole process controls the highest temperature below 800 DEG C, effectively avoiding deep graphitization phenomenon.
[0026] In some specific embodiments, the metal is aluminum or copper.
[0027] The melting point of copper is about 1083 DEG C, and the welding temperature is generally selected to be below 1400 DEG C in vacuum, and lower in the presence of oxygen. Active brazing or diffusion welding is often used, and the core is to improve the interface bonding by active elements.
[0028] The reactivity of copper itself with diamond (carbon) is very low, and active metals such as titanium (Ti), chromium (Cr) or zirconium (Zr) can be added to the copper-based filler. These elements can chemically react with the carbon on the surface of the diamond to form stable carbides (such as TiC, Cr3C2), forming a "diamond-carbide-copper" strong interface, and significantly improving the wettability of copper to diamond.
[0029] Active brazing: use Cu-Ti (such as Cu-10Ti), Cu-Cr and other filler materials, heat to 900-1050 DEG C (below the melting point of copper, use the filler to melt and wet), and keep for several minutes. The active elements Ti / Cr diffuse to the surface of the diamond and form a carbide layer, realizing the bonding.
[0030] Diffusion bonding: Copper and diamond surface are combined by atomic diffusion at high temperature (800-1000℃) and high pressure. Active elements can be coated on the diamond surface to promote interfacial reaction.
[0031] Copper and diamond welding joint is commonly used for the substrate (copper-based) combination of diamond tools (such as grinding wheel, saw blade), which requires temperature control and holding time to avoid graphitization of diamond due to long time high temperature; vacuum environment can prevent copper oxidation and diamond surface pollution.
[0032] Among them, the melting point of aluminum is lower (about 660℃), and the thermal damage to diamond is smaller, but the aluminum surface is easy to form a dense oxide film (Al2O3), and the reactivity of aluminum and carbon is extremely weak, and the wettability is extremely poor, so the welding difficulty is higher, and brazing, diffusion welding or laser welding is often used.
[0033] The welding of copper and aluminum generally needs to break the oxide film + introduce transition layer operation.
[0034] Remove the oxide film: Al2O3 on the surface of aluminum will hinder welding, which needs to be removed by physical (such as mechanical polishing, ultrasonic cleaning) or chemical (such as fluoride flux) method, or heated in vacuum / inert atmosphere to make the oxide film crack.
[0035] Introduce active transition layer: Direct welding is difficult to combine, and an active metal (such as Ti, Cr) or alloy coating is deposited on the surface of diamond in advance to form a carbide transition layer (such as TiC), and then welded with aluminum. The transition layer can be prepared by magnetron sputtering, evaporation and other methods, and the thickness is usually several microns.
[0036] Brazing (including transition layer): After Ti plating on the surface of diamond, aluminum-based filler (such as Al-Si alloy) is used, and heated to 600-650℃ in vacuum or Ar atmosphere. After the filler melts, it wets the TiC transition layer and aluminum matrix to realize the combination.
[0037] Diffusion bonding: At high temperature (500-600℃) and high pressure, aluminum and transition layer (TiC) are combined by atomic diffusion. The pressure needs to be enough to make the aluminum matrix and the transition layer in close contact.
[0038] Laser welding: The high energy density of laser is used to rapidly heat and locally melt aluminum and react with the Ti pre-plated diamond surface, which shortens the high temperature time and reduces oxidation.
[0039] Aluminum matrix light weight, aluminum and diamond welding joint, suitable for diamond tools (such as aerospace grinding tools) that require weight reduction. Note: the thermal expansion coefficient of aluminum and diamond is large (aluminum is about 23×10 -6 / ℃, diamond is about 1×10 -6The welding is prone to residual stress after welding, which may cause interface cracking and needs to be relieved by controlling the thickness of the transition layer or annealing treatment.
[0040] Optionally, the wavelength of the femtosecond laser is 1000-1100 nm, the pulse width is 200-300 fs, and the repetition frequency is 100-500 kHz.
[0041] In this alternative embodiment, by combining femtosecond pulse width and specific wavelength, a controllable thickness of the graphite layer is generated while maintaining the integrity of the diamond substrate, and the setting of the repetition frequency window avoids the interface stress concentration caused by heat accumulation in traditional high-frequency laser processing. The thickness uniformity deviation of the graphitized layer on the diamond surface is less than 5%, the interface bonding strength is increased to 1.8 times of that of the traditional method, and the heat-affected zone depth is controlled to be less than 500 nanometers, effectively avoiding the performance degradation of the diamond body caused by high temperature phase transition.
[0042] Specifically, the wavelength refers to the spatial length of the oscillation period of the laser beam, which can be realized by using a titanium-sapphire laser or a fiber laser to output a near-infrared beam. This wavelength matches the diamond lattice vibration energy level, promoting the transfer of photon energy to the lattice vibration energy state. The pulse width refers to the energy release duration of a single laser pulse, which can be realized by generating sub-picosecond pulses using chirped pulse amplification technology. By limiting the heat diffusion path length, non-thermal dominated phase transition occurs on the diamond surface. The repetition frequency refers to the number of laser pulses emitted per unit time, which can be realized by adjusting the pulse sequence density using an acousto-optic modulator. By controlling the energy injection rate per unit area, the heat accumulation effect is suppressed.
[0043] When the wavelength is selected to be 1000-1100 nanometers, the diamond surface layer electrons are excited by a multi-photon absorption mechanism, and the sp 3 hybridization of the surface layer carbon atoms is changed to sp 2 hybridization. When the pulse width is 200-300 femtoseconds, the electron-phonon coupling time scale is compressed, so that the diamond lattice completes graphite phase nucleation before thermal relaxation is completed. When the repetition frequency is set to 100-500 kHz, the interval time between adjacent pulses is greater than the electron-phonon relaxation period but less than the thermal diffusion time constant, which ensures that the phase transition reaction proceeds sufficiently and limits the heat-affected zone to within 200 nanometers of the surface.
[0044] Optionally, the energy density during the scanning process is 5-15 J / cm 2 , the scanning speed is 100-500 mm / s, and the spot overlap rate is 50-70%.
[0045] In this optional embodiment, by precisely defining the interaction relationship of three key parameters, the uniformity and density of the graphite layer structure are significantly improved under the premise of avoiding thermal damage to the substrate. The problem of unstable graphite layer quality caused by improper parameters during femtosecond laser processing of diamond surface is solved. Through the synergistic control of energy density, scanning rate and spot overlap rate, a continuous and uniform graphite layer structure is formed, which effectively guarantees the interfacial bonding strength between the subsequent magnetron sputtering active layer and the diamond substrate, and avoids the delamination failure caused by interface defects during high temperature service.
[0046] Specifically, the energy density refers to the energy delivered by laser pulses per unit area, which can be realized by adjusting the ratio of laser power to spot size. This parameter range can cause a controllable graphitization reaction on the diamond surface, avoiding thermal damage to the substrate caused by too low energy leading to discontinuous graphite layer or too high energy. The scanning rate refers to the speed of laser beam moving on the diamond surface, which can be realized by adjusting the moving speed of the laser processing platform. This parameter range balances the processing efficiency and thermal accumulation effect, preventing excessive ablation caused by too low speed or insufficient graphitization caused by too high speed. The spot overlap rate refers to the overlap ratio between adjacent laser scanning tracks, which can be realized by adjusting the ratio of scanning path distance to spot diameter. This parameter range ensures effective coverage between scanning tracks and eliminates the gap between untreated areas.
[0047] By limiting the energy density to 5 to 15 J / cm 2 , a continuous and uniform graphite layer can be formed on the diamond surface, avoiding local non-graphitization caused by insufficient energy or substrate micro-cracks caused by excessive energy. When the scanning rate is set to 100 to 500 mm / s, the heat input during single scanning process is within a controllable range, and thermal accumulation caused by too slow moving speed leading to diamond phase transition or too fast speed leading to incomplete graphitization reaction is avoided. When the spot overlap rate is controlled within the range of 50 to 70%, the adjacent spot areas form sufficient overlap, eliminating the gap between scanning paths and ensuring the uniform and dense surface morphology of the graphite layer, providing a defect-free substrate for the stable deposition of subsequent active elements.
[0048] Optionally, step S2 comprises: Magnetron sputtering of a first active element as a bonding layer on the surface of the graphite layer, followed by deposition of a second active element as a diffusion barrier layer, and the combination of the bonding layer and the diffusion barrier layer as an active layer.
[0049] In the optional embodiment, by setting the diffusion barrier layer, the element diffusion is limited while the interface bonding force is maintained, so that the interface reaction product thickness is controlled within a reasonable range, and the micro-cracks are avoided. The problem of insufficient interface bonding strength between the active layer and the diamond is effectively solved, and the interface defects caused by element diffusion during high-temperature heat treatment are inhibited. The composite active layer structure realizes the stability of the interface metallurgical bonding through the gradient transition design, and provides a reliable transition interface for subsequent brazing.
[0050] Specifically, the bonding layer refers to an active metal layer formed on the surface of the graphite by a magnetron sputtering process, and one or more elements of titanium, chromium, tungsten or zirconium can be used to realize the bonding layer. The role of the bonding layer is to enhance the interface bonding strength through chemical bonding with carbon elements. The diffusion barrier layer refers to an active metal layer deposited on the surface of the bonding layer, and the same or different active elements can be used to realize the diffusion barrier layer. One or more elements of Mo, W or Zr can be used to realize the diffusion barrier layer. The role of the diffusion barrier layer is to inhibit the excessive diffusion of metal atoms during high-temperature brazing through a dense structure.
[0051] By constructing the composite active layer structure in stages, the bonding layer is first formed on the surface of the graphite layer formed by laser modification, and the first active element is used to form a stable interface bonding with carbon through chemical affinity. Then, the diffusion barrier layer is deposited on the surface of the bonding layer, and a continuous and dense structure is formed by controlling the sputtering parameters to limit the migration of the second active element during subsequent brazing. The bonding layer and the graphite layer on the surface of the diamond establish a strong bonding interface through chemical bonding, and the diffusion barrier layer reduces the interface reaction rate at high temperature through physical barrier effect. The synergistic effect of the two-layer structure not only ensures the mechanical strength of the interface bonding, but also avoids the generation of brittle phases at the interface caused by excessive diffusion of active elements.
[0052] Optionally, the first active element is one or more of Ti, Cr, W and Zr, and the second active element is one or more of Mo, W and Zr.
[0053] In the optional embodiment, by combining the strong carbide-forming elements and high-melting-point metals, the thermodynamic driving force of the interface reaction is ensured, and the grain boundary migration at high temperature is inhibited through the diffusion barrier mechanism, so that the interface maintains a dense structure within the range of 500-800℃. The problem of insufficient bonding strength between the active layer and the graphite layer on the surface of the diamond is solved. The continuous gradient structure is formed by the carbide transition layer and the diffusion barrier layer formed during brazing, which effectively reduces the interface thermal stress concentration and avoids the interface failure caused by metal atom penetration in high-temperature environment, and ensures the long-term service reliability of the diamond and metal joint. The active element system of Ti, Cr, W and Zr is suitable for the existing magnetron sputtering production line and has strong compatibility.
[0054] Specifically, the active element refers to a metal material capable of forming a stable compound with carbon atoms, and can specifically use the first active element Ti, Cr, W and Zr as the bonding layer material to achieve a negative value of the enthalpy of formation of carbide, which is combined with the graphite layer in the interface reaction. The second active element Mo, W and Zr refers to a refractory metal with a high melting point, and can specifically use a magnetron sputtering deposition process to form a diffusion barrier layer to achieve its crystal structure to inhibit the high-temperature migration of metal atoms.
[0055] When Ti or Cr is formed as a bonding layer on the graphite layer formed by femtosecond laser modification on the diamond surface by magnetron sputtering, the atoms thereof react with the graphite carbon atoms to generate TiC or Cr3C2 phase, forming a continuous metallurgical bonding interface. Mo, W or Zr is deposited as a diffusion barrier layer on the surface of the bonding layer, and its hexagonal close-packed or body-centered cubic crystal structure can effectively block the penetration and diffusion of metal elements during brazing. When the two functional layers work together, the bonding layer provides the interface bonding strength, and the diffusion barrier layer maintains the structural stability at high temperature, and together prevents interface cracks or delamination.
[0056] Optionally, the vacuum degree during the process of magnetron sputtering of the first active element as the bonding layer is not more than 5×10 -4 Pa, the substrate temperature of the diamond is 150 to 250°C, the sputtering power is 80 to 150 W, and the sputtering time is 30 to 120 min.
[0057] In this optional embodiment, through the synergistic control of vacuum degree, substrate temperature, sputtering power and time, an active layer structure with no pollution, high density and chemical bonding is formed at the interface. The pollution of impurity gas to the first active element in the magnetron sputtering process is effectively inhibited, the chemical bonding between the active layer and the diamond surface is strengthened, the micro-crack defects caused by discontinuous film layer or stress concentration are avoided, and the shear strength of the diamond and the metal interface after brazing is improved to the level that can withstand high-temperature cyclic load.
[0058] Specifically, the vacuum degree is not more than 5×10 -4Pa refers to the residual gas pressure control range of the chamber in the magnetron sputtering process, which can be realized by using a molecular pump and a mechanical pump system. This vacuum degree condition can inhibit the reaction of impurity gases such as oxygen and nitrogen with active elements, and avoid the formation of oxide or nitride inclusions at the interface. The substrate temperature of 150 to 250°C refers to the temperature range of the diamond heated during the sputtering process, which can be realized by a built-in resistance heater in the substrate table. This temperature interval can promote the diffusion and migration of active element atoms to the graphite layer on the diamond surface, while avoiding excessive temperature that causes thermal stress cracks in the diamond or excessive decomposition of the graphite layer. The sputtering power of 80 to 150 W refers to the radio frequency power range applied to the magnetron target material, which can be realized by adjusting the output of the radio frequency power supply. This power range can control the ionization rate and deposition rate of active elements, so that the film layer forms a dense and uniform microstructure. The sputtering time of 30 to 120 min refers to the duration of the magnetron sputtering process, which can be controlled by a programmed timer. This time range ensures that the active elements form a continuous and thickness-controllable adhesive layer on the diamond surface.
[0059] In the magnetron sputtering process, the vacuum degree is maintained at 5×10 -4 Pa order of magnitude, the mean free path of gas molecules remaining in the chamber increases significantly, and the collision probability of active element atoms with gas molecules during sputtering decreases, thereby reducing the formation of pore defects in the film layer. When the substrate temperature is controlled at 150 to 250°C, the active element atoms obtain sufficient kinetic energy to penetrate the contaminants adsorbed on the surface of the graphite layer, and at the same time, a local diffusion reaction occurs with the carbon atoms on the diamond surface to form a chemical bonding interface. When the sputtering power is set to 80 to 150 W, the plasma density and sputtering yield of the target material surface reach a balanced state, avoiding island growth defects caused by too low power that results in slow film deposition rate, and avoiding interface peeling caused by too high power that results in stress accumulation in the film layer. When the sputtering time is set to 30 to 120 min, the active elements are uniformly deposited at a thickness of 0.3 to 1.0 μm to form a continuous barrier layer that can effectively block the penetration of liquid metal during brazing.
[0060] Alternatively, the vacuum degree during the process of depositing the second active element as a diffusion barrier layer is not more than 5×10 -4 Pa, the deposition power is 80 to 150 W, and the deposition time is 30 to 120 min.
[0061] In this optional embodiment, the problem of micro-cracks caused by insufficient interfacial bonding strength of the active layer and the diamond is effectively solved. By optimizing the combination of deposition process parameters, a diffusion barrier layer with high purity and low defects is formed on the diamond surface, which forms a stable chemical bond with the lower graphite structure, and effectively inhibits the lateral diffusion of metal elements to the diamond side during high-temperature brazing, thereby maintaining the integrity of the interface structure.
[0062] Specifically, vacuum level refers to the gas pressure state within the chamber during the deposition process. This can be achieved using high-vacuum magnetron sputtering equipment, where a multi-stage vacuum pump assembly works in conjunction with a sealed chamber to create the target vacuum environment. This parameter aims to reduce the interference of residual gas molecules on the deposition process and prevent reactive elements from reacting with impurity gases to form non-target compounds.
[0063] The deposition power refers to the energy input level applied to the target material during magnetron sputtering, which can be achieved by adjusting the power supply output. This parameter controls the kinetic energy of the sputtered particles, ensuring they form stable chemical bonds with the graphite layer upon impact with the substrate without causing interface damage due to excessive energy.
[0064] The deposition time refers to the process duration for active elements to accumulate on the substrate surface to form a continuous thin film, which can be achieved by setting the equipment's timing program. This parameter controls the thickness and density of the diffusion barrier layer, ensuring that it effectively blocks the diffusion and penetration of metal elements during subsequent brazing while avoiding interlayer stress concentration caused by excessive deposition.
[0065] Vacuum degree not greater than 5×10 -4 When deposition is performed at Pa, the mean free path of residual gas molecules increases significantly, reducing the probability of collisions between active element particles and gas molecules during flight, thus maintaining a high-purity deposition state. When the deposition power is maintained in the range of 80 to 150 W, sputtered particles gain sufficient kinetic energy to penetrate impurities adsorbed on the graphite layer surface and form stable chemical bonds with carbon atoms, while avoiding excessively high power that could lead to excessive particle bombardment energy and damage to the already formed interface structure. When the deposition time is controlled within the range of 30 to 120 minutes, a diffusion barrier layer of uniform thickness can be formed. The lower limit of this time ensures the formation of a continuous and dense film structure, while the upper limit prevents excessive accumulation of active elements from causing lattice distortion.
[0066] Optionally, the thickness of the adhesive layer is 0.2 to 1.0 μm, and the thickness of the diffusion barrier layer is 0.2 to 1.0 μm.
[0067] In this optional embodiment, by limiting the thickness range in two ways, a balance is established between enhanced interfacial reaction and diffusion inhibition, solving the problems of insufficient bonding strength and microcracks caused by thickness mismatch in traditional processes. This achieves a stable chemical bonding interface between the active layer and the diamond substrate, effectively preventing excessive diffusion of metal atoms during brazing, significantly reducing the probability of microcracks forming at the interface after high-temperature heat treatment, and improving the long-term service reliability of the diamond-metal brazed joint.
[0068] Specifically, the bonding layer refers to a deposition layer of active elements formed on the surface of the graphite layer by a magnetron sputtering process, and can be implemented by using one or more elements of titanium, chromium, molybdenum, tungsten or zirconium, which functions to form a carbide strengthening phase by metallurgical reaction with the graphite layer to enhance the interfacial bonding strength. The diffusion barrier layer refers to a deposition layer of active elements on the surface of the bonding layer, which can be implemented by using the same or different active elements as the bonding layer, and functions to inhibit the penetration and diffusion of metal atoms in the brazing process by physical barrier effect to prevent the generation of micro-cracks caused by excessive interfacial reaction.
[0069] Specifically, the lower limit of the thickness of the bonding layer can ensure sufficient active elements to participate in the interfacial reaction to form a continuous carbide strengthening phase, avoiding unreacted areas in the bonding interface due to insufficient thickness; and the upper limit of the thickness of the bonding layer can avoid stress concentration caused by a too thick brittle carbide layer. The lower limit of the thickness of the diffusion barrier layer can effectively block the diffusion and penetration of metal atoms in the filler metal to prevent the interface from losing control under high temperature; and the upper limit of the thickness of the diffusion barrier layer can avoid weakening the metallurgical bonding between the bonding layer and the filler metal due to a too thick barrier layer. The coordinated control of the thickness of the two layers not only maintains the stability of the interfacial chemical bonding, but also inhibits the interfacial defects caused by high-temperature diffusion through physical barrier effect.
[0070] Optionally, the vacuum degree in the process of vacuum heat treatment is not more than 5x10 -4 Pa, and the treatment time is 30 to 90 min.
[0071] In this optional embodiment, the dual problems of interface pollution and reaction control are solved by precise matching of vacuum degree and time, which realizes the strengthening of the interface by vacuum heat treatment, and ensures that the interfacial reaction is fully completed and the thermal damage to the diamond is minimized through time optimization, so as to finally obtain a diamond / metal joint with high bonding strength and high reliability.
[0072] Specifically, the vacuum degree refers to the degree of vacuum of the heat treatment environment, which can be implemented by using a high-vacuum furnace combined with a multi-stage vacuum pump set to inhibit the pollution of oxygen and impurity gases to the interface by maintaining a high-vacuum environment. The treatment time refers to the duration of the diamond under high temperature, which can be implemented by a temperature control system and a timing device, and the risk of interfacial reaction and thermal damage is balanced by setting a time window.
[0073] When the vacuum degree is not more than 5x10 -4Under the condition of Pa, the oxidation reaction of the active element and the diamond surface at the interface is effectively inhibited, thereby avoiding the bonding defects caused by the decrease in wettability. When the processing time is set to 30 to 90 minutes, the active element and the graphite layer on the diamond surface can sufficiently diffuse to form a carbide bonding layer, while avoiding excessive conversion of the diamond crystal structure to the graphite phase due to too long time. The synergistic effect of the vacuum environment and the time parameter enables the interface metallurgical reaction to be completed within a controllable range, thereby guaranteeing the bonding strength and maintaining the thermodynamic stability of the diamond.
[0074] Another embodiment of the present application provides a diamond / metal joint made by the brazing method of the diamond based on femtosecond laser modification and metal as described above.
[0075] In this embodiment, the diamond surface is formed with chemical active sites by femtosecond laser pretreatment, the composite active layer structure and the low-temperature brazing process are combined, the interface bonding strength is improved, and high-temperature damage is avoided.
[0076] The interface bonding force of the diamond / metal joint is significantly enhanced, a stable carbide bond is formed between the active layer and the diamond matrix, and delamination failure during high-temperature service is effectively inhibited; the brazing temperature is reduced to below 800 degrees Celsius, thereby avoiding the degradation of the thermal conductivity of the diamond due to graphitization; the composite active layer structure maintains the interface stability during brazing, thereby preventing the decrease in joint strength caused by the generation of brittle phases.
[0077] Specifically, the femtosecond laser modification refers to the process of inducing carbon structure transformation on the diamond surface by using an ultrashort pulse laser, which can be achieved by scanning a laser beam with a wavelength in the range of 1000 to 1100 nanometers, and the graphite layer is formed by rearranging carbon atoms to provide chemical bonding sites for subsequent active element deposition. The active layer refers to a composite structure including a bonding layer and a diffusion barrier layer, which can be achieved by sequentially depositing active metal elements using a magnetron sputtering process. The bonding layer enhances the interface bonding force through carbide reaction, and the diffusion barrier layer inhibits high-temperature element diffusion. The low-temperature brazing refers to a joining process performed in the range of 500 to 800 degrees Celsius, which can be achieved by heating and holding in a vacuum environment, and the temperature range is controlled to avoid damage to the diamond due to graphitization.
[0078] The diamond surface is treated by femtosecond laser scanning to form a graphite layer, the surface inertness is effectively reduced, and the active elements deposited by magnetron sputtering can form stable chemical bonds with carbon atoms. The bonding layer and the graphite layer establish strong interface bonding through carbide reaction, and the diffusion barrier layer limits the migration of active elements into the filler material during brazing, thereby preventing the generation of brittle phases. The brazing temperature is controlled to be lower than that of the conventional process, and the metallurgical bonding is completed in a vacuum environment, thereby avoiding the degradation of the thermal conductivity of the diamond due to high temperature and reducing the interface residual stress.
[0079] The application will be further described in connection with specific embodiments.
[0080] Example 1, brazing method of diamond and metal based on femtosecond laser modification.
[0081] I. Diamond surface pretreatment: 10x10x0.5 mm chemical vapor deposition diamond (CVD diamond) film was sequentially immersed in acetone and ethanol for ultrasonic cleaning for 5 min to remove organic contaminants; II. A femtosecond laser was used to scan and treat the surface of the diamond to form a graphite layer on the surface of the diamond, the wavelength of the femtosecond laser was 1000 nm, the pulse width was 200 fs, the repetition frequency was 500 kHz, and the femtosecond laser treatment parameters were energy density: 12 J / cm 2 , scanning rate: 300 mm / s, and spot overlap rate: 60%; III. The substrate temperature of the diamond was 200°C, and an active element Cr was magnetron sputtered on the surface of the graphite layer, the sputtering power was 90 W, the sputtering time was 120 min, and a 1 μm thick Cr active layer was obtained; IV. Under the condition of a vacuum degree of 5x10 -4 Pa, heat treatment was performed at 600°C for 60 min, a Cr3C2 layer was formed at the interface of the diamond, and then the diamond was brazed with the metal.
[0082] Example 2, brazing method of diamond and metal based on femtosecond laser modification.
[0083] I. Diamond surface pretreatment: CVD diamond film was sequentially immersed in acetone and ethanol for ultrasonic cleaning for 8 min to remove organic contaminants; II. A femtosecond laser was used to scan and treat the surface of the diamond to form a graphite layer on the surface of the diamond, the wavelength of the femtosecond laser was 1030 nm, the pulse width was 250 fs, the repetition frequency was 300 kHz, and the femtosecond laser treatment parameters were energy density: 15 J / cm 2 , scanning rate: 100 mm / s, and spot overlap rate: 50%; III. The substrate temperature of the diamond was 250°C, and an active element W was magnetron sputtered on the surface of the graphite layer, the sputtering power was 150 W, the sputtering time was 30 min, and a 300 nm thick W active layer was obtained; IV. Under the condition of a vacuum degree of 5x10 -4 Pa, heat treatment was performed at 500°C for 90 min, a WC layer was formed at the interface of the diamond, and then the diamond was brazed with the metal.
[0084] Example 3, brazing method of diamond and metal based on femtosecond laser modification.
[0085] I. Diamond surface pretreatment: sequentially immerse a chemical vapor deposition diamond (CVD diamond) film in acetone and ethanol for ultrasonic cleaning for 10 min to remove organic contaminants; II. Scan the diamond surface using a femtosecond laser to form a graphite layer on the diamond surface, the wavelength of the femtosecond laser is 1030 nm, the pulse width is 300 fs, the repetition frequency is 200 kHz, and the femtosecond laser processing parameters are energy density: 8 J / cm 2 , scanning rate: 300 mm / s, and spot overlap rate: 60%; III. The substrate temperature of the diamond is 200°C, and an active element Ti is magnetron sputtered on the surface of the graphite layer, the sputtering power is 150 W, the sputtering time is 30 min, and a 250 nm thick Ti active layer is obtained; IV. Under the condition of a vacuum degree of 5x10 -4 Pa, heat treatment at 800°C for 30 min forms a TiC layer at the diamond interface, and then the diamond is brazed with the metal.
[0086] Example 4, brazing method of diamond and metal based on femtosecond laser modification.
[0087] I. Diamond surface pretreatment: sequentially immerse a chemical vapor deposition diamond (CVD diamond) film in acetone and ethanol for ultrasonic cleaning for 10 min to remove organic contaminants; II. Scan the diamond surface using a femtosecond laser to form a graphite layer on the diamond surface, the wavelength of the femtosecond laser is 1050 nm, the pulse width is 300 fs, the repetition frequency is 400 kHz, and the femtosecond laser processing parameters are energy density: 10 J / cm 2 , scanning rate: 400 mm / s, and spot overlap rate: 50%; III. The substrate temperature of the diamond is 200°C, and an active element Zr is magnetron sputtered on the surface of the graphite layer, the sputtering power is 150 W, the sputtering time is 30 min, and a 250 nm thick Zr active layer is obtained; IV. Under the condition of a vacuum degree of 5x10 -4 Pa, heat treatment at 800°C for 30 min forms a ZrC layer at the diamond interface, and then the diamond is brazed with the metal.
[0088] Example 5, brazing method of diamond and metal based on femtosecond laser modification.
[0089] I. Diamond surface pretreatment: the CVD diamond film was immersed in acetone and ethanol for ultrasonic cleaning for 10 min, respectively, to remove organic contaminants; II. A femtosecond laser was used to scan the surface of the diamond to form a graphite layer, the wavelength of the femtosecond laser was 1100 nm, the pulse width was 300 fs, the repetition frequency was 100 kHz, the femtosecond laser processing parameters were energy density: 5 J / cm 2 , scanning rate: 500 mm / s, and light spot overlap rate: 70%; III. The substrate temperature of the diamond was 150℃, a Cr active element was magnetron sputtered on the surface of the graphite layer, the sputtering power was 90W, the sputtering time was 90 min, a 800 nm thick Cr adhesive layer was obtained, and then a W active element was magnetron sputtered, the sputtering power was 120W, the sputtering time was 60 min, and a 300 nm thick W diffusion barrier layer was obtained; IV. The diamond interface formed a Cr3C2 layer under the condition of a vacuum degree of 10 -4 Pa at 800℃ for 30 min, and then the diamond was brazed with the metal.
[0090] Comparative Example 1, brazing method of diamond and metal.
[0091] I. Diamond surface pretreatment: a 10×10×0.5 mm CVD diamond film was immersed in acetone and ethanol for ultrasonic cleaning for 5 min, respectively, to remove organic contaminants; II. The substrate temperature of the diamond was 200℃, a Cr active element was magnetron sputtered on the surface of the diamond, the sputtering power was 90W, the sputtering time was 120 min, and a 1 μm thick Cr active layer was obtained; IV. The diamond interface formed a Cr3C2 layer under the condition of a vacuum degree of 5×10 -4 Pa at 600℃ for 60 min, and then the diamond was brazed with the metal.
[0092] Comparative Example 2, brazing method of diamond and metal.
[0093] I. Diamond surface pretreatment: a CVD diamond film was immersed in acetone and ethanol for ultrasonic cleaning for 8 min, respectively, to remove organic contaminants; II. The substrate temperature of the diamond was 250℃, a W active element was magnetron sputtered on the surface of the diamond, the sputtering power was 150W, the sputtering time was 30 min, and a 300 nm thick W active layer was obtained; III. The diamond interface formed a W3C layer under the condition of a vacuum degree of 5×10 -4The diamond interface forms a WC layer under the condition of 500℃ and 90 min heat treatment under 5×10
[0094] Comparative Example 3, brazing method of diamond and metal.
[0095] I. Diamond surface pretreatment: CVD diamond film pieces were sequentially immersed in acetone, ethanol ultrasonic cleaning for 10 min, and organic contaminants were removed. II. The substrate temperature of the diamond was 200℃, and the active element Ti was magnetron sputtered on the surface of the diamond, the sputtering power was 150W, and the sputtering time was 30 min, obtaining a 250 nm thick Ti active layer. III. Under the condition of 5×10 -4 The diamond interface forms a TiC layer under the condition of 800℃ and 30 min heat treatment under 5×10
[0096] Comparative Example 4, brazing method of diamond and metal.
[0097] I. Diamond surface pretreatment: CVD diamond film pieces were sequentially immersed in acetone, ethanol ultrasonic cleaning for 10 min, and organic contaminants were removed. II. The substrate temperature of the diamond was 200℃, and the active element Zr was magnetron sputtered on the surface of the diamond, the sputtering power was 150W, and the sputtering time was 30 min, obtaining a 250 nm thick Zr active layer. III. Under the condition of 5×10 -4 The diamond interface forms a ZrC layer under the condition of 800℃ and 30 min heat treatment under 5×10
[0098] Effect implementation example The graphite layer increases the reaction area of the active element by more than 300%, and the critical bonding strength of the Cr3C2 layer and the diamond in Example 1 and Comparative Example 1 is tested respectively, and the test method adopts scratch test. The test results are that the critical bonding strength of the Cr3C2 layer and the diamond in Example 1 is 11 MPa, and the critical bonding strength of the Cr3C2 layer and the diamond in Comparative Example 1 is 0.2 MPa.
[0099] The critical bonding strength of the WC layer and the diamond in Example 2 and Comparative Example 2 is tested respectively, and the test method adopts scratch test. The test results are that the critical bonding strength of the WC layer and the diamond in Example 2 is 3 MPa, and the critical bonding strength of the WC layer and the diamond in Comparative Example 2 is 0.1 MPa.
[0100] The critical bonding strength of the TiC layer and diamond in Example 3 and Comparative Example 3 was tested respectively, and the test method adopted scratch test. The test results were that the critical bonding strength of the TiC layer and diamond in Example 3 was 8 MPa, and the critical bonding strength of the TiC layer and diamond in Comparative Example 3 was 0.5 MPa.
[0101] The critical bonding strength of the ZrC layer and diamond in Example 4 and Comparative Example 4 was tested respectively, and the test method adopted scratch test. The test results were that the critical bonding strength of the ZrC layer and diamond in Example 4 was 4 MPa, and the critical bonding strength of the ZrC layer and diamond in Comparative Example 4 was 0.2 MPa.
[0102] It can be seen that femtosecond laser can realize non-thermal precise etching of diamond surface, induce sp 3 Carbon to sp 2 Graphite phase transformation, controllable formation of nanometer graphite transition layer, significantly improve the surface chemical activity, and significantly enhance the chemical bonding strength of active element layer (Ti, Cr, W or Zr, etc.) and diamond. The active element and the nanometer graphite layer react to form a continuous active element-C compound (about ΔG_f = -180 kJ / mol), which has a lattice partially coherent with diamond (lattice mismatch degree < 5%), realizing strong metallurgical bonding; at the same time, from the thermodynamic point of view, the Gibbs free energy of the reaction of active element and graphite layer is much lower than that of the reaction of active element and diamond, so the nanometer graphite layer will reduce the thermodynamic requirement of active element-C, and promote the interface reaction to realize stronger interfacial bonding The diamond interface of Example 1 formed a Cr3C2 layer, and an electron microscope was used to take a picture, as shown in Figure 2 , forming a graphite transition layer.
[0103] The diamond of Example 1 was detected before being treated by femtosecond laser, and the Raman spectrum was obtained, as shown in Figure 3 , there was a clear characteristic peak (D peak) representing diamond at 1332 cm -1 ; the diamond was detected after being treated by femtosecond laser, and the Raman spectrum was obtained, as shown in Figure 4 , in addition to the diamond characteristic peak, a typical graphite characteristic peak was formed at 1580 cm -1 , confirming the generation of graphite layer.
[0104] The diamond interface of Example 1 formed a Cr3C2 layer, and a cross-section transmission electron microscope was used to take a picture, as shown in Figure 5 , a continuous Cr3C2 layer was formed at the interface, with a thickness of about 150 nm.
[0105] Although the present application has been disclosed with reference to the above embodiments, the application is not limited to the above embodiments. It will be apparent to those skilled in the art that various changes and modifications can be made thereto without departing from the spirit and scope of the application, and it is intended to include all such changes and modifications as fall within the scope of the application.
Claims
1. A brazing method for diamond and metal based on femtosecond laser modification, characterized in that, Includes the following steps: S1: A femtosecond laser is used to scan the surface of the diamond to form a graphite layer on the diamond surface; S2: Magnetron sputtering of active elements onto the surface of the graphite layer to deposit an active layer; S3: The diamond is subjected to vacuum heat treatment at 500 to 800°C, and then the diamond is brazed to the metal.
2. The brazing method for diamond and metal based on femtosecond laser modification according to claim 1, characterized in that, The femtosecond laser has a wavelength of 1000 to 1100 nm, a pulse width of 200 to 300 fs, and a repetition frequency of 100 to 500 kHz.
3. The brazing method for diamond and metal based on femtosecond laser modification according to claim 1, characterized in that, The energy density during the scanning process is 5 to 15 J / cm². 2 The scanning rate is 100 to 500 mm / s, and the spot overlap rate is 50 to 70%.
4. The brazing method for diamond and metal based on femtosecond laser modification according to claim 1, characterized in that, Step S2 includes: A first active element is magnetron sputtered onto the surface of the graphite layer as a binder layer, and a second active element is then deposited as a diffusion barrier layer. The binder layer and the diffusion barrier layer are combined to form the active layer.
5. The brazing method for diamond and metal based on femtosecond laser modification according to claim 4, characterized in that, The first active element is one or more of Ti, Cr, W and Zr, and the second active element is one or more of Mo, W and Zr.
6. The brazing method for diamond and metal based on femtosecond laser modification according to claim 4, characterized in that, The vacuum degree during the magnetron sputtering process where the first active element is used as the binder layer is no greater than 5 × 10⁻⁶. -4 Pa, wherein the substrate temperature of the diamond is 150 to 250°C, the sputtering power is 80 to 150 W, and the sputtering time is 30 to 120 min.
7. The brazing method for diamond and metal based on femtosecond laser modification according to claim 4, characterized in that, The vacuum degree during the deposition of the second active element as a diffusion barrier layer is no greater than 5 × 10⁻⁶. -4 Pa, deposition power of 80 to 150 W, and deposition time of 30 to 120 min.
8. The brazing method for diamond and metal based on femtosecond laser modification according to claim 4, characterized in that, The thickness of the adhesive layer is 0.2 to 1.0 μm, and the thickness of the diffusion barrier layer is 0.2 to 1.0 μm.
9. The brazing method for diamond and metal based on femtosecond laser modification according to claim 1, characterized in that, The vacuum degree during the vacuum heat treatment process shall not exceed 5 × 10⁻⁶. -4 Pa, processing time is 30 to 90 minutes.
10. A diamond / metal connector, characterized in that, It is manufactured using the brazing method for diamond and metal based on femtosecond laser modification as described in any one of claims 1-9.
Citation Information
Cited By
Welding process of high-strength cutter alloy steel and ceramic composite layer
CN121946000A